Non-Synonymous Single-Nucleotide Polymorphisms and Physical Activity Interactions on Adiposity Parameters in Malaysian Adolescents - Zaharan, Nur Lisa; Muhamad, Nor Hanisah; Jalaludin, Muhammad Yazid; Su, Tin Tin; Mohamed, Zahurin; Mohamed, M. N. A.; A. Majid, Hazreen (Frontiers in Endocrinology, 2018)
Background: Several non-synonymous single nucleotide polymorphisms (nsSNPs) have been shown to be associated with obesity. Little is known about their associations and interactions with physical activity (PA) in relation to adiposity parameters among adolescents in Malaysia. Methods: We examined whether a) PA and b) selected nsSNPs are associated with adiposity parameters and whether PA interacts with these nsSNPs on these outcomes in adolescents from the Malaysian Health and Adolescents Longitudinal Research Team study (MyHeARTs) (n=1,151). BMI, waist-hip-ratio and percentage body fat (%BF) were obtained. PA was assessed using Physical Activity Questionnaire for Older Children (PAQ-C). Five nsSNPs were included; ADRB3 rs4994, FABP2 rs1799883, GHRL rs696217, MC3R rs3827103 and VDR rs2228570, individually and as combined genetic risk score (GRS). Associations and interactions between nsSNPs and PAQ-C scores were examined using Generalized Linear Model. Results: PAQ-C scores were associated with %BF (β=-0.44[95%CI -0.72,-0.16], p=0.002).The CC genotype of ADRB3 rs4994 (β=-0.16[-0.28,-0.05], corrected p=0.01) and AA genotype of MC3R rs3827103 (β=-0.06[-0.12,-0.00], p=0.02) were significantly associated with %BF compared to TT and GG genotype respectively. Significant interactions with PA were found between ADRB3 rs4994 (β=-0.05[-0.10,-0.01], p=0.02) and combined GRS β=-0.03[-0.04,-0.01], p=0.01) for %BF. Conclusion: Higher physical activity score was associated with reduced %BF in Malaysian adolescents. Of the nsSNPs, ADRB3 rs4994 and MC3R rs3827103 were associated with %BF. Significant interactions with PA were found for ADRB3 rs4994 and combined GRS on %BF but not on measurements of weight or circumferences. Targeting body fat represent prospects for molecular studies and lifestyle intervention in this population.